SAS 9.4 macro language : reference (SAS Institute Inc., 2015)
"Explaining how to increase the modularity, flexibility, and maintainability of your SAS code using the SAS macro facility, this book provides complete information about macro language elements, interfaces between the SAS macro facility and other parts of SAS software, and macro processing in general."--